Strategy of UUS BTN Post SPIN OFF with Scenario Planning Approach - Fariani, Aida; Jayaprawira, Acep; Bintoro, Oni Bibin (The Indonesian Journal of Business Administration, 2013)
The research objective is to build a strategy UUS BTN post spin off in order to reach sustainability growth. Tools used to formulate the strategi is scenario planning after analyzing external & internal factors thru environmental scanning and research methods used are study literature, stakeholder's in depth interview and secondary data published. The outcome of scenario planning will be used for strategic action necessary due to the one that is recommended for UUS BTN’s strategy post spin off. The objective of UUS BTN post spin off strategy is using scenario generation to help planners to influence and enhance the quality of strategic planning. From in depth interview, it is obvious, the expectation of parent bank after spin off, which are two things UUS need to concern namely: achieving better performance with the status BUS, than still UUS status and process of internal consolidation of post spin-off takes place smoothly. As an early warning signal, the sinergi UUS BTN has with Bank BTN is not optimal yet. Bank BTN’s network in cooperation with PT. Pos Indonesia with on line real time outlets at the Post Office branches through out Indonesia, as much as 2,728 units, none if it has sharia services. Other than that, based on the results of a survey conducted by the Bureau of Research Infobank PingFans put KPR BTN top position with index 2,743 (Infobank, 2012:11), meanwhile for KPR iB, KPR BTN iB does not count at, eventhough for the realization FLPP 2010-2011, according to data from Kemenpera is the largest supplier, with 114,235 units valued at Rp 3.81 trillion, followed by KPR BTN iB 6,184 units worth Rp 222.32 billion (Clipping Housing, 2012). Limitation of this in depth interview research method needs to be continued by Delphi method as it was a preliminary research.Keywords: strategy, spin off, Islamic banking, scenario planning